A model of full bloom starting date of some white Vitis vinifera L. varieties grown in Helvecia - Ladányi, M.; Hlaszny, E. (International Journal of Horticultural Science, 2010)
Grapevine bloom happens between end of May and the middle of June in Hungary. However, climate change in the past decades and the occurring weather anomalies can modi fy this date to a diverse degree. Among the weather factors, the bloom starting dates of grapevine depend mostly on temperature and relative humidity of air. There can be significant differences between North American and East Asian grapevine varieties, and of course, the early and late ripening varieties. ln this approach we investigated the starting dates of bloom between 2000 and 2004 for grapevine varieties grown in Helvecia, as well as the effectiveness of a temperature sum model. The model is based on the widely accepted cumulated heat sum concept, and the optimization was made for the least standard deviation in days as well as on the least average absolute deviation in days and on the least maximum deviation in days. The model is connected directly to a similar model for the budburst date of the same plantings (Hlaszny & ladanyi, 2009). We set the optimum lower base temperature to I 0.45 °C and the upper base temperature to 26 °C. The absolute values of the differences between the observations and the model estimations move between one and six days with an average of 1.81 days